2012
DOI: 10.1177/147323001204000206
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Codon 72 Polymorphism with Hepatocellular Carcinoma: A Meta-Analysis

Abstract: 446OBJECTIVE: The association between codon 72 polymorphism of the tumour protein p53 (TP53) gene -which results in a missense mutation of arginine (R) to proline (P) -and susceptibility to hepatocellular carcinoma (HCC) is controversial. A metaanalysis was performed in order to define this relationship more precisely. METHODS: Published studies of TP53 codon 72 polymorphism and the risk of HCC were identified. Data were extracted, and summary odds ratios (OR) and 95% confidence intervals (95% CI) were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
8
2
Order By: Relevance
“…Mutations of the p53 gene may result in loss of its tumor suppressor function and thus contribute to the carcinogenesis and/or tumor progression. The polymorphism of p53 codon 72, a transversion of G to C (Arg to Pro), has been shown to be related to the risk of some malignant tumors [79]. It has been confirmed that the two polymorphic variants, Arg and Pro, of p53 codon 72 differ biochemically and biologically [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of the p53 gene may result in loss of its tumor suppressor function and thus contribute to the carcinogenesis and/or tumor progression. The polymorphism of p53 codon 72, a transversion of G to C (Arg to Pro), has been shown to be related to the risk of some malignant tumors [79]. It has been confirmed that the two polymorphic variants, Arg and Pro, of p53 codon 72 differ biochemically and biologically [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Six of these articles were excluded including 3 publications containing overlapping data [26][28], and 3 were meta-analyses [13], [17], [18]. Manual search of references cited in the published studies did not reveal any additional articles.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to MDM2 SNP309 polymorphism, a meta-analysis by Ma et al [13] found that the MDM2 SNP309 polymorphism was associated with an increased HCC risk in Asians and Caucasians, however, they failed to include all eligible studies in the meta-analysis [14], [15], [16], which make their conclusions questionable. With respect to TP53 R72P polymorphism, two meta-analyses [17], [18] investigating the same hypothesis, quite similar in methods and performed almost at the same time, yielded different conclusions. Furthermore, the two previous meta-analyses did not cover all eligible studies.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, gene-gene and gene-environmental factors interactions were not fully addressed in this meta-analysis for the lack of sufficient data. HBV, HCV and several gene polymorphisms, such as P53 codon72, GSTM1 and GSTT1, are associated with liver cancer, and there may be gene-gene or gene-environmental factors interactions (Wang et al, 2010, Ding et al, 2012. However, we could not perform gene-gene and gene-environmental analyses owing to the limited reported information on such associations in the included studies.…”
Section: Discussionmentioning
confidence: 99%